Process components of the implicit association test a diffusion-model analysis. [article]. - Klauer, Karl Christoph
The authors present a diffusion-model analysis of the Implicit Association Test (IAT). In a study 1, the IAT effect was decomposed into 3 dissociable components : Relative to the compatible phase (a)ease and speed of information accumulation are lowered in the incompatible phase, (b)more cautions speed-accuracy settings are adopted, and (c)nondecision components of processing require more time. Studies 2 and 3 assessed the nature of interindividual differences in these components. Construct-specific variance in the IAT relating to the construct to be measured (such as implicit attitudes) was concentrated in the compatibility effect on information accumulation (Studies 2 and 3), wheras systematic method variance in the IAT was mapped on differential speed-accuray settings (Study 3). Implications of these dissociations for process theories of the IAT and for applications are discussed. -- (from the author)